Perbedaan Tingkat Kemandirian Belajar Ditinjau Dari Metode Pembelajaran pada Anak - Pratitis, Nindia (Persona:Jurnal Psikologi Indonesia, 2018)
This study aims to determine whether there are differences in learning independence in terms of learning methods in children. Subjects in this study consisted of children aged 6-12 years amounted to 84 people, which is divided into two groups where the first group is a child using student centered learning method while the second group is a group that uses teacher centered learning method learning. Data collecting tool is a self-learning questionnaire prepared by the author. The questionnaire consisted of 36 items of statement items. The data analysis was done by independent sample t test technique with the help of SPSS version 17 statistic program. The result of data analysis showed that there was a significant difference of learning independence level in terms of learning method in children where children using student centered learning method have higher learning independence level than children using teacher centered learning method. Keywords: Learning Independence, Learning Method